ANALISIS EKONOMI RUMAHTANGGA PETANI TANAMAN PANGAN DI PROVINSI LAMPUNG - Ratna Winandi Asmarantaka (Jurnal Agribisnis dan Ekonomi Pertanian, 2007)
Agricultural sector still plays a strategic and dominant role in employment, although the structure of employment is dominated by small-scale farmers where their labor productivity is about 25.0 percent of the non-agricultural sector. The target of agricultural development (Agricultural Revitalization) is the farm household. Therefore, it is interesting to study the farm household economic behavior, especially the farm households that cultivate food crop in Lampung Province. The objective of this study is to analyze the structure and economic behavior of the farm households in the villages that planted food crops (rice and cassava) in Lampung Province. The analytical methods used in this paper were tabulation analysis, test of differences (Duncan’s test) and econometric methods using simultaneous equations.The results showed that the income structure of rice village mainly came from agriculture, whereas that of cassava village came from non-agriculture. The use of family labor to earn living has not fulfilled the Central Statistics Bureau criteria for fulltime workers, even though it has met the criteria of food security. In the rice village, the investment (education and health expenditures) and saving of the farm households were influenced significantly by and responsive against the agricultural income, whereas consumption was influenced by the number of family members. On the other hand, in the cassava village, investment (education and health expenditures) and saving of the farm households were influenced by and responsive relatively against the non agricultural income and total income, whereas consumption also are influenced by the non agricultural income and the number of family members, although not responsive.